A Promising Partnership: Uncovering the Middle Ground Between Social Innovation and Social Work: Response to Dr. Marilyn L. Flynn's Remarks. (March 2017) - Sensoy Bahar, Ozge
This response article discusses opportunities to bridge social work and social innovation as a promising partnership to address the issues impacting vulnerable populations across the global context. It starts by revisiting the conceptualization of innovation in social work and continues by considering factors that contribute to the growing interest in social innovation and related concepts. This article concludes by discussing differences in social work and social innovation and how these differences can be turned into opportunities for a fruitful partnership that can push both fields forward.